PLUTONIUM LABORATORY DECONTAMINATION EXPERIENCE. (United States. Dept. of Energy ; distributed by the Office of Scientific and Technical Information, U.S. Dept. of Energy, 1967)
Glove Boxes/explosion And Fire In, Contamination Of Laboratory And Equipment By Plutonium--uranium Oxides Spread By; Laboratories/decontamination Procedures For, Contaminated By Plutonium--uranium Oxides In Glove Box Explosion And Fire; Laboratory Equipment/decontamination Procedures For, Contaminated By Plutonium--uranium Oxides In Glove Box Explosion And Fire; Laboratory Furniture/decontamination Procedures For, Conta; Decontamination/methods For Plutonium Laboratory, After Glove Box Explosion And Fire; Protective Clothing/ Use In Decontamination Of Plutonium Laboratory After Glove Box Explosion And Fire; Uranium Oxides Uo$sub 2$/puo$sub 2$--uo$sub 2$, Contamination Of Equipment And Laboratory By, From Glove Box Explosion And Fire; Plutonium Oxides Puo$sub 2$/puo$sub 2$--uo$sub 2$, Contamination Of Equipment And Laboratory By, From Glove Box Explosion And Fire; Building Materials/decontamination Procedures For, Contaminated By Plutonium--uranium Oxides In Glove Box Explosion And Fire.